Medieval architecture - Nicola Coldstream (Oxford University Press, 2002)
Medieval architecture comprises much more than the traditional image of Gothic cathedrals and the castles of chivalry. A great variety of buildings--synagogues, halls, and barns--testify to the diverse communities and interests in western Europe in the centuries between 1150 and 1550. This book looks at their architecture from an entirely fresh perspective, shifting the emphasis away from such areas as France towards the creativity of other regions, including central Europe and Spain. Treating the subject thematically, Coldstream seeks out what all buildings, both religious and secular, have in common, and how they reflect the material and spiritual concerns of the people who built and used them. Furthermore, the author considers how and why, after four centuries of shaping the landscapes and urban patterns of Europe, medieval styles were superseded by classicism